Efeitos da adição de Dynamic tape® a um programa de exercícios com carga progressiva em sujeitos com tendinopatia patelar: um ensaio clínico randomizado - Ferreira, Shalimá Figueirêdo Chaves Coêlho (2022)
Patellar tendinopathy (PT) mainly affects athletes in jumping sports and is characterised by pain and dysfunction in the patellar tendon. The most indicated treatment for PT is conservative treatment, which should be based on exercises with progressive loading. The elastic Dynamic Tape (DT) bandage has been used in clinical practice with the objective of accelerating the tendon rehabilitation process and facilitating the load absorption process, reducing PT pain. However these effects have not yet been proven with scientific studies. The aim of this study was to verify the additional effects of adding DT to an exercise program with progressive loading in subjects with patellar tendinopathy. A clinical trial was conducted with 48 subjects clinically diagnosed with PT, who were randomly allocated into two groups: Group A, which did progressive exercises and received application of DT; Group B, which did progressive exercises and received placebo bandage application. The intervention was performed 3 times a week and lasted a maximum of 12 weeks. The primary outcomes evaluated were: PT severity degree, evaluated through VISA-P scale; PT pain when squatting on inclined plane, evaluated through visual analogue scale. The secondary outcomes were: threshold of pain to pressure, evaluated with a pressure algometer; global perceived effect, evaluated through the global perceived effect scale; and adherence to treatment, evaluated through the frequency in the face-to-face consultations. The result of this research demonstrated that there are no additional effects of adding (TD) to an exercise program with progressive load in subjects with PT